Os objetos digitais de aprendizagem na prática pedagógica de matemática em uma escola pública estadual de São Paulo - Gomes, Vanderley Pereira (2017)
This research analyzes the use of Digital Learning Objects (ODA) in the pedagogical practice of teacher-researcher in a Public Middle School. Therefore, it is sought to understand how the learning environment is constituted from a research-intervention of the mathematics teacher when using the ODA, such as games, simulators and using laptops in classroom activities with the perspective of innovating their practice education. The research was based on audio and video recordings and images of classes, in which the students were pedagogically oriented to solve problem situations of mathematical contents using the ODA of the Curriculum + platform of the Education Department of the State of São Paulo, from participatory and reflexive forms. The results show that the students have participated actively in the classes when the technology appears as an adjunct to the process, considering that the intervention and reflection of the teacher were necessary so that the knowledge is actually constructed and socialized. It was also found that when the students were submitted to organize the mathematical thinking of the activities, of the ODA applyed, they presented difficulties in the organization and resolution of the questions. Thus, the study pointed out the need for the school, through its teachers, to incorporate new teaching strategies and to add to its Political Pedagogical Project concrete actions which make pedagogical technology viable in the classroom environment.